Diplomacy and Covid-19: A Reflection - Albert Triwibowo (Jurnal Ilmiah Hubungan Internasional, 2020)
During the pandemic of covid-19, it is interesting to see how diplomacy play its part as a method of communication, and whether it supports the creation of mutual understanding between states. This article tries to reflect what is happened in regard to diplomacy from the end of December 2019, when Chinese authorities confirmed a new virus to the WHO, until the middle of April 2020. In order to give a clearer picture, this article will look on how countries respond in dealing with the pandemic of covid-19. This article argues that countries’ responses so far reflect that diplomacy does not happen in a constructive manner as states are facing a new kind of challenge. As a result, diplomacy tend to have more nationalistic sentiment, and not respond as part of international society. For Indonesia, it would be important to play its role in regional context, as ASEAN would be an important regional organization to fight the pandemic. As part of international society, diplomacy should be used as a method of communication that based on values of goodwill, solidarity and humanity, especially to find mutual understanding in multilateral context. Diplomacy also should be used to communicate for exchange of goods, people, information, services, and best practices in order to fight global problems.